Perinatal and neonatal outcomes in gestational diabetes: The importance of the number of abnormal values in an oral glucose tolerance test - Sanna Eteläinen; Elina Keikkala; Shilpa Lingaiah; Matti Viljakainen; Tuija Männistö; Anneli Pouta; Risto Kaaja; Johan G. Eriksson; Hannele Laivuori; Mika Gissler; Eero Kajantie; Marja Vääräsmäki (Acta Obstetricia et Gynecologica Scandinavica)
Abstract Introduction Gestational diabetes mellitus (GDM) is defined by one or more abnormal values in an oral glucose tolerance test (OGTT). The significance/importance of the number of abnormal values in relation to adverse perinatal and neonatal outcomes is unclear. We assessed the association of these outcomes with the number of abnormal glucose values in a 2‐h 75 g OGTT in a large register‐based cohort. Material and Methods This sub‐study of the Finnish Gestational Diabetes Study was based on the Finnish Medical Birth Register 2009 supplemented with OGTT laboratory data of 4869 pregnant women from six Finnish hospitals. The diagnostic cut‐offs in OGTT according to the Finnish guidelines for plasma samples were ≥5.3 mmol/L (fasting), ≥10.0 mmol/L 1 h or ≥8.6 mmol/L 2 h after the glucose load. As per the guidelines, women with one or several abnormal OGTT values received diet and lifestyle counseling in the primary care, self‐monitored their glucose values and received pharmacological therapy as needed. Women with GDM were categorized according to the number of abnormal glucose values. The primary outcomes, composites of adverse perinatal (pre‐eclampsia, preterm delivery, macrosomia or primary cesarean section) and neonatal outcomes (birth trauma, neonatal hypoglycemia, hyperbilirubinemia or stillbirth/perinatal mortality), were analyzed by logistic regression adjusted for maternal age, pre‐pregnancy body mass index, parity, socio‐economic status and smoking. Results Of all the women, 877 (18.0%) had one, 278 (5.7%) two and 79 (1.6%) three abnormal OGTT values, while 3635 (74.7%) women were normoglycemic. Women with at least two abnormal OGTT values had higher proportions of adverse perinatal composite (35.0% vs. 27.5%, adjusted odds ratio 1.36; 95% confidence interval 1.03–1.81) and neonatal composite outcomes (31.1% vs. 18.9%, adjusted odds ratio 1.88; 95% confidence interval 1.40–2.52) compared to women with one abnormal value. The risks of delivery induction and neonatal hypoglycemia were increased regardless of the number of abnormal values when compared with normoglycemic women. Conclusions The risk of adverse perinatal and neonatal outcomes is significantly higher in women with two or more abnormal OGTT values than in those with one abnormal value.